IMPROVING ABILITY TO KNOW THE CONCEPTS OF EARLY CHILDREN'S PATTERNS THROUGH DIFFERENTIATE LEARNING - Putri Diana Sofiya Hidayah Putri; Rachma Hasibuan; Desi Kartika Fatmawati (LPPM Universitas PGRI Adi Buana Surabaya, 2023)
This study aims to improve the ability to recognize the concept of patterns in early childhood through differentiation learning at Pembina State Kindergarten, Mojokerto City. This type of research is action research carried out in two cycles. The subjects in this study were children aged 5-6 years with a total of 16 children consisting of 10 girls and 6 boys. Data collection techniques in this study used performance, while data analysis in this study used descriptive statistical analysis. The results of this study indicate that there is an increase in the ability to recognize pattern concepts through differentiated learning, namely the percentage of completeness in cycle I is (33.3 percent) with information that children are still confused about and often ask about the sequence of patterns that have been explained by the teacher. The increase in cycle II was (85.42) percent, with information that children were faster, precise, thorough, and independent in drawing up patterns. The conclusion from this study is that the activities of the differentiated learning model can improve the ability to recognize the concept of patterns in early childhood.